THE ROLE OF THE HIDDEN CURRICULUM IN DEVELOPING DISCIPLINE ATTITUDES OF FIFTH-GRADE ELEMENTARY SCHOOL STUDENTS: A CASE STUDY - Sama'; Adi Atmoko; Ratna Ekawati (Universitas Majalengka, 2026)
The low discipline of elementary school students, which is reflected in delays, irregularities in following classroom procedures, and weak adherence to school norms, shows that the formation of discipline cannot depend on formal instruction and written regulations alone. In basic education, the internalization of disciplinary values takes place through implicit daily experiences. This study aims to analyze the role of hidden curriculum in shaping the discipline attitude of grade V elementary school students and identify supporting and inhibiting factors for its implementation. This study uses a qualitative approach with a case study design. Data was collected through participatory observation, in-depth interviews, and documentation review, then analyzed using the Miles, Huberman, and Saldaña interactive model that included reduction, presentation, and verification of data repeatedly. The results of the study show that hidden curriculum operates through three main mechanisms, namely the daily routine of the school, the role model of teachers, and social norms that are not written in the classroom culture. These three mechanisms synergistically shape student discipline behavior, including punctuality, adherence to procedures, academic independence, and the ability to self-regulate social interactions. Supporting factors include the stability of school culture and teacher commitment, while inhibiting factors include inconsistency in disciplinary practices, diversity of family backgrounds, and limited facilities. This study concludes that hidden curriculum has a strategic role in building student discipline in a natural, humanistic, and sustainable manner through strengthening the culture of habituation in elementary schools. This study provides empirical evidence regarding the operational mechanism of hidden curriculum in the formation of discipline in Indonesian elementary schools.